Serious incident prevention how to achieve and sustain accident-free operations in your plant or company - Burns, Thomas, 1946- (Amsterdam ; Boston : Gulf Professional Pub., 2002)
Serves as a guide to creating a proactive, effective prevention process. This book presents a model showing you how to systematically identify and execute the steps needed to make your operations incident-free. It includes cases of real-life examples and safety performance scorecards.
Serious incident prevention: A career perspective. The improvement challenge. The barriers to improvement. Management of change. A proven process improvement model. Establishing serious incident prevention as an organizational priority. Employee involvement. Understanding the risks. Identifying the critical work. Establishing performance standards. Measurement and feedback. Reinforcement and corrective action. Improving and updating the process. Applying the process model: A case study. Responding to the challenge.
Includes bibliographical references and index.
Keywords: Industrial safety; Accidents -- Prevention; Electronic books